Dark tourism: A bibliometric review of the past, present and future trends - Muhammad Ashraf, Fauzi (University of Rijeka, 2023)
Purpose – The purpose of this study is to critically review the knowledge structure of dark tourism. It is an emerging tourism attraction, but one that has received less attention in the literature. The fundamental difference between dark tourism and other forms of tourism is the deeply rooted association with death and mortality, which is considered a distinctive element of the tourist attraction. Despite the role that gloom tourism plays in the economic development of tourism, its function as an economic resource for the local community needs to be further explored and evaluated. With this in mind, this study conducts a science mapping based on a bibliometric analysis to uncover the knowledge structure of the phenomenon based on recognized publications in the field. Methodology/Design/Approach – Drawing from the opportunity of dark tourism, this paper analyzes the knowledge structure based on two bibliometric analyses to uncover the past, present and future trends in dark tourism. 592 journal publications were extracted and analyzed from the Web of Science (WoS) core collection database. Findings – The results indicate that the clusters that emerged from the analyzes focus on the foundations of dark tourism, motivations for visiting dark sites, and specific interest in war/ battlefield tourism. This research shows that dark tourism benefits each segment of society in different ways by making it possible to experience the pain and suffering of the dead, the dark and agonizing events of past generations. Implications for theory and practice are discussed to further develop the field into a sustainable tourism segment. Originality of the research – This study provides the state-of-the-art knowledge structure analysis of the dark tourism phenomenon